Implementasi Kepemimpinan Kepala Sekolah dalam Rangka Pelaksanaan Manajemen Berbasis Sekolah di Madrasah Tsanawiyah Negeri 1 Prabumulih - Hasmi Ermi Yani; Yasir Arafat; Mulyadi Mulyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to find out how the implementation of the principal's leadership in the context of implementing school-based management of Madrasah Tsanawiyah. This research was conducted at the Madrasah Tsanawiyah Negeri 1 Prabumulih school, which is located on Jalan Angkatan 45 Muaradua Village, East Prabumulih District, Prabumulih City. This research uses Qualitative Research with descriptive method. The objects or informants in this study are principals, teachers, administrative staff, students, parents, committees and the surrounding community. Data collection techniques in this study used in-depth interview, observation and documentation techniques. Data analysis techniques use qualitative data analysis including data collection, data reduction, data display and data verification. The result of this research is that the principal has implemented his leadership in carrying out school-based management in Madrasah Tsanawiyah Negeri 1 Kota Prabumulih, by conducting curriculum programs, fulfilling infrastructure and effective supervision. The fundamental difference of this study is in the research subjects that took place in the Tsanawiyah Madrasah. Keywords: Implementation; Leadership; Principal; MBS